Isolation, Molecular Characterization, and Antimicrobial Resistance of Selected Culturable Bacteria From Crayfish (Procambarus clarkii) - Huang, Zixian; Li, Yuanyuan; Cai, Chang; Dong, Ning (Frontiers in Microbiology, 2022)
Red swamp crayfish (Procambarus clarkii) have become one of the favorite aquatic products in China. The modern farming mode which uses antibiotics to prevent diseases could impact the bacteria in crayfish intestines. Here, we determined the distribution and antimicrobial resistance phenotypes of the selected culturable bacteria in crayfish intestines and characterized an isolate with last-line antibiotic resistance determinant. Totally, 257 strains were isolated from 115 crayfish. These strains were highly diverse, with Citrobacter sp. (n = 94, 36.6%) and Aeromonas sp. (n = 88, 34.2%) being dominant. Other isolates belonged to genera Pseudomonas, Myroides, Morganella, Klebsiella, Acinetobacter, Proteus, Enterobacter, Kluyvera, and Escherichia. Most strains from crayfish were susceptible to all tested antibiotics. None of the isolates carried last-line antibiotic resistance genes except one Escherichia coli isolate with blaNDM-5 was detected, which is the first report of blaNDM-5-positive E. coli isolate from red swamp crayfish. Whole-genome sequencing suggested it belonged to ST48 and carried several resistance genes. blaNDM-5 was located within an Tn3000-like transposon linked to an external 5 bp sequence (ACTAT) on both sides on a IncHI1B/HI1A/FIA multi-replicon plasmid. This transposon was considered to be acquired by replicative transposition mediated by IS3000. The emergence of bacteria with last-line antibiotic resistance genes in crayfish poses serious threat to public health since crayfish could act as a reservoir for the transfer of resistance to humans.